Design of English electronic lectures for teaching chapter “Gases”, Physics 10th grade - Lê, Thị Ánh Tuyết (Trường Đại học Sư Phạm - Đại học Đà Nẵng, 2019)
Research the theoretical and practical basis of the topic. Consult expert. Design of English lesson plans, study cards, homework. Design of English electronic lectures for teaching chapter “Gases”. Design of the rubric to evaluate the quality of electronic lectures.